Management of a Pediatric Patient With a Left Ventricular Assist Device and Symptomatic Acquired von Willebrand Syndrome Presenting for Orthotopic Heart Transplant. (December 2020) - Flannery, Kaitlin M; Kamra, Komal; Maeda, Katsuhide; Shuttleworth, Paul; Almond, Christopher; Navaratnam, Manchula
We present the successful perioperative management of an 11-year-old patient presenting for heart transplant with a left ventricular assist device, symptomatic acquired von Willebrand syndrome, and recent preoperative intracranial hemorrhage. A brief review of the pathophysiology of acquired von Willebrand syndrome is included. As the number of pediatric patients supported with ventricular assist devices continues to increase, the management of symptomatic acquired von Willebrand syndrome during the perioperative period is an important consideration for anesthesiologists.